A new Holocene relative sea-level curve for western Brittany (France): Insights on isostatic dynamics along the Atlantic coasts of north-western Europe. (1st December 2015) - Goslin, Jérôme; Van Vliet Lanoë, Brigitte; Spada, Giorgio; Bradley, Sarah; Tarasov, Lev; Neill, Simon; Suanez, Serge
Abstract: This study presents new Relative Sea Level (RSL) data that were obtained in the Finistère region (Western tip of Brittany, France) and the implications those data have for the understanding of the isostatic dynamics across north-western Europe, and more specifically along the Atlantic and Channel coasts. New stratigraphic sequences were obtained and analyzed to derive 24 new Sea-level Index Points, in which 6 are basal. These new data considerably increase the knowledge we have of the RSL evolution along the coasts of Western Brittany since the last 8 kyr B.P. From this new dataset, RSL was estimated to rise continuously over the last 8 kyr with a major inflection at ca. 6 kyr cal. BP. Our results show large vertical discrepancies between the RSL records of Brittany and South-Western UK, with the latter plotting several meters below the new data. From this comparison we suggest that the two regions underwent a very different pattern and/or amplitude of subsidence during the last 8 kyr which has implications for the spatial and temporal pattern of the peripheral bulge of the European ice sheets. We compared our data against predictions from Glacio-Isostatic Adjustment models (GIA models). There are large misfits between RSL observations and the predictions of the global (ICE-5G (VM2a) – Peltier, 2004, GLAC1-b – Tarasov and Peltier, 2002; Tarasov et al., 2012, Briggs et al., 2014) and regional UK models ("BIIS" – Bradley et al., 2009; Bradley et al., 2011; "Kuchar"- Kuchar et al., 2012), which can't be resolved through significant changes to the deglaciation history and size of the British–Irish Ice sheet. Paleo-tidal modelling corrections indicate regional changes in the tidal ranges played a negligible role in the data-model misfits. Hence, we propose that the misfits are due to some combination of: (i) unaccounted mass-loss of far-field ice-sheets (Antarctic ice-Sheet or Laurentide Ice-Sheet), (ii) unresolved differences in the deglaciation history and size of the Fennoscandian Ice sheet or, more likely, (iii) significant lateral variations in the Earth's structure across the English Channel. Highlights: We present extensive new Holocene RSL data for the Western-Brittany region (France). RSL rose continuously over the last 8 kyrs B.P., with a major inflexion ca. 6 kyr B.P. Large vertical offsets are observed between RSL record from Brittany and SW UK. Large misfits are observed between our RSL data and the predictions of GIA models. Several hypotheses are proposed and tested to explain these discrepancies. Changes in regional tidal ranges surely played a minor role. Lateral variations in the Earth's structure are most probable.